Double immunostaining for maspin and p53 on cell blocks increases the diagnostic value of biliary brushing cytology. Issue 2 (10th January 2017) - Kanzawa, Maki; Sanuki, Tsuyoshi; Onodera, Manabu; Fujikura, Kohei; Itoh, Tomoo; Zen, Yoh
Abstract : Our objective is to elucidate the usefulness of maspin/p53 double immunostaining on biliary brushing cytology specimens. We first examined the expression of maspin in the biliary epithelium with variable degrees of dysplasia using surgically resected specimens (n = 56). Maspin appeared to be overexpressed in a stepwise manner from benign to malignant cholangiocytes: the reactive epithelium (20%), biliary intraepithelial neoplasia ( 50%), and invasive cholangiocarcinomas (>90%). Next, an automated sequential double immunostaining protocol for maspin and p53 was applied to paraffin‐embedded cell blocks of the biliary brushing cytology specimens obtained from 58 consecutive patients. Cell block preparation was successful in 44 cases (76%), which were morphologically diagnosed as adenocarcinoma (n = 16), atypical cells not diagnostic for malignancy (n = 10), and benign (n = 18). Double positive cells were observed in 14/16 (88%) morphologically malignant, 6/10 (60%) borderline, and 0/18 benign cases. All 20 positive cases were proven to have pancreatobiliary malignancies by subsequent imaging or pathological analyses. A similar staining protocol for S100P and p53 was also applied to the same cohort; however, the positive frequency was slightly lower than those of maspin and p53 (36% vs. 45%). In conclusion, Maspin/p53 double immunostaining on cell blocks contributes to the detection of malignant cells in biliary brushing cytology specimens.